2010
DOI: 10.1159/000321257
|View full text |Cite
|
Sign up to set email alerts
|

Do Smooth Waters Run Deep? Alcohol Intoxication and the Effects of Water Consumption on Driving-Related Cognitions and Behavior

Abstract: The present study tested the effect of the combined use of alcohol and water on driving-related cognitions and behavior. Seventy-four female students performed a driving simulator task after having consumed alcohol or a placebo. Additionally, half of the participants consumed 0.5 liter of water. It was hypothesized that combining alcohol and water could lead to an underestimated perceived intoxication level resulting in more favorable driving cognitions and increased risk behavior. Our findings showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…A significantly higher mean speed was reported in alcoholic groups in comparison with control groups 5, 10. But no significant difference was reported in the studies by Spaanjaars et al 16 and Fillmore et al 18 …”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…A significantly higher mean speed was reported in alcoholic groups in comparison with control groups 5, 10. But no significant difference was reported in the studies by Spaanjaars et al 16 and Fillmore et al 18 …”
Section: Resultsmentioning
confidence: 83%
“…Also in the studies by Rakauskas et al 8 and Marczinski et al, 12 we found no mean and standard deviation (SD) values for LPSD. However, based on these studies in Table 3, SD values of lane position was significantly higher in alcoholic groups in comparison with non-alcoholic groups, except in the studies by Rakauskas et al, 8 Fillmore et al 18 and Spaanjaars et al 16 …”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations